ANALISIS PENGARUH KUALITAS SIMDA (SISTEM INFORMASI MANAJEMEN KEUANGAN DAERAH) TERHADAP KINERJA BENDAHARA PADA PEMERINTAH DAERAH KOTA TERNATE - Suharli Manoma (Jurnal Manajemen Sinergi, 2016)
Local Government of Ternate City chose to use system issued by BPKP that is SIMDA. Ease in using SIMDA is to assist Local Government in implementing local financial management, data speed and accuracy. To know the influence of quality of SIMDA to Performance of Treasurer at Pemeritah of Ternate City. The location where the author's research is SKPD within the scope of Ternate city government. Respondents of this study amounted to 120 people. This research uses Simple Linear Regression data analysis. The result of the analysis by using regression test obtained significant value of 0.003 or less than the value of probability (p-value) 0,05 (0,003 0,05) this means that independent variable that quality of SIMDA have significant influence simultaneously to the Treasurer's performance. Quality of Regional Financial Management Information System has a significant effect on the performance of treasurer work in Ternate Municipal Government.